Running Head: Situating The Social Studies Situating The Social Studies Curriculum In John Dewey’s Theory Of Nature: Promise And Possibility - Stuckart, Daniel W. (European Scientific Journal, ESJ, 2016)
No subject matter comes closer to modeling Deweyan philosophy than the modern social studies. Yet, social studies scholars have been debating for decades whether Dewey actually supported the curriculum resulting in a perceived paradox between Dewey’s interdisciplinary approach to problem solving and his writings about traditional, stand-alone social sciences. This paper situates the problem in Dewey’s Theory of Nature and argues that (1) the paradox is a myth; (2) Dewey is misunderstood and marginalized in the literature; and (3) Dewey offers a middle position for addressing problems and supporting social studies learning with myriad theories.